2019
DOI: 10.26540/ijgsr.v6.i1.2019.127
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Phytoplanktons in Undasa Wetland with reference to indicator organisms

Abstract: Wetlands are vital for human survival. They are among the world's most productive environments. The phytoplanktonic diversity is very important for the conservation of freshwater ecosystem. A total of 30 species out of which 13 species belongs to chlorophyceae, 3 to Euglenophyceae, 8 to Bacillariophyceae, 6 to Cyanophyceae. The result indicates that the maximum number of genera occurred during summer (11-17) followed by winter (5-18) and monsoon season (6-9) respectively. Ankistrodesmus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…from the temple and several thousands of pilgrims take holy bath. Jatwa et al (2018), from Undasa wetland observed that Undasa wetland receives a considerable amount of domestic water waste and sewage from nearby urban and rural areas. Sahebkhedi lake is moderate polluted, but this waterbody is unfit for drinking purpose without proper treatment.…”
Section: Resultsmentioning
confidence: 99%
“…from the temple and several thousands of pilgrims take holy bath. Jatwa et al (2018), from Undasa wetland observed that Undasa wetland receives a considerable amount of domestic water waste and sewage from nearby urban and rural areas. Sahebkhedi lake is moderate polluted, but this waterbody is unfit for drinking purpose without proper treatment.…”
Section: Resultsmentioning
confidence: 99%